MEMBANGUN LITERASI HUKUM DAN PENDIDIKAN DALAM MASYARAKAT - Prasetio, Zallu Dwi; Setiawan; Ariffin, Muchammad (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2024)
Despite having various educational facilities, the community still faces major challenges regarding legal literacy and understanding the importance of education. Therefore, the aim of this PKM is to increase legal awareness and facilitate the community with basic knowledge that can support their daily lives. This programme applies a participatory approach that involves all levels of society in every activity. With this approach, it is expected to educate the community about basic legal rights, the importance of education, and build awareness about better social management. In addition, this activity also introduces practical ways to address social issues such as promiscuity among teenagers, which is often a hindrance to their development. Hopefully, through this PKM, the community of Sungai Purun Kecil Village can better understand the role of education and law in creating a more organised and prosperous life. This programme aims to encourage the creation of a community that is more independent, educated, and aware of their legal rights.